2019
DOI: 10.1002/jper.19-0228
|View full text |Cite
|
Sign up to set email alerts
|

6‐Shogaol, an active ingredient of ginger, inhibits osteoclastogenesis and alveolar bone resorption in ligature‐induced periodontitis in mice

Abstract: BackgroundPeriodontitis is an inflammatory disease of the tissues surrounding teeth that causes destruction of connective tissues. During the progress of periodontitis, osteoclasts are solely accountable for the resorption of alveolar bones that leads to the loss of teeth if not properly treated. Thus, the development of effective anti‐resorptive therapies will greatly benefit the treatment of periodontitis patients. In the present study, we suggest an inhibitory effect of 6‐shogaol, an ingredient of ginger, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
1
21
0
1
Order By: Relevance
“…Administration of 6-shogaol prevented osteoclastogenesis and alveolar bone resorption caused by ligature-induced periodontitis, decreased the number of macrophages and neutrophils, and considerably downregulated the expression of IL-1β and TNF-α in periodontal tissue. These results confirmed that 6-shogaol had anti-osteoclastogenic effects and suggested its potential application as an anti-resorptive treatment in periodontitis [233].…”
Section: Effects Of Natural and Synthetic Compoundssupporting
confidence: 73%
“…Administration of 6-shogaol prevented osteoclastogenesis and alveolar bone resorption caused by ligature-induced periodontitis, decreased the number of macrophages and neutrophils, and considerably downregulated the expression of IL-1β and TNF-α in periodontal tissue. These results confirmed that 6-shogaol had anti-osteoclastogenic effects and suggested its potential application as an anti-resorptive treatment in periodontitis [233].…”
Section: Effects Of Natural and Synthetic Compoundssupporting
confidence: 73%
“… 86 In an animal periodontitis model, treatment with 6-shogaol reduces the macrophage numbers, avoids bone destruction, inhibits the osteoclast maturation and activation, and downregulates IL-1β, TNF-α, and ROS. 87 Similarly, 6-gingerol prevents osteoclast differentiation and represses IL-1-induced PGE2 synthesis in mouse osteoblasts. 88 Moreover, zingerone restores the renal functions and declines the generation of TNF-α, IL-1β, IL-6 and ROS in animal models of nephropathy.…”
Section: Anti-inflammatory Immunomodulatory and Anti-oxidative Potentials Of Gingermentioning
confidence: 99%
“…Moreover, it is believed that ginger exerts potent anti‐oxidant functions by scavenging ROS and restoring the balance between anti‐oxidant/oxidant homeostasis (Reddy et al., 2014; Shanmugam et al., 2011). Recent research has shown that 6‐shogaol is one of the main active ingredients of ginger (Kim et al., 2020). Based on previous findings, 6‐shogaol rich ginger extract may lead to an improved antioxidant defense system via the induction of HO‐1 and the nuclear factor E2‐related factor2 (Nrf2)/antioxidant response element (ARE) pathway.…”
Section: Discussionmentioning
confidence: 99%